PENGARUH MEDIA PEMBELAJARAN MELALUI KETERAMPILAN BERBICARA SISWA MATA PELAJARAN BAHASA INDONESIA DI MADRASAH IBTIAIYAH AN-NUR KABUPATEN MAGELANG - Oktradiksa, Ahwy; Fitriansyah, Agung (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
This research aims to know the influence of the media learning through speaking skills students in Indonesia language subjects MI An-Nur Deyangan Magelang Regency. The population in this research is the student's MI An-Nur Deyangan totaling 142 students. As for the sample of the study amounted to 18 students are determined by means of the purposive sampling technique. The method of data collection in this research method using question form for either variable or variable learning media speaking skills. The technique of data analysis in this study uses the analysis of product moment. To know the influence of the media against learning speaking skills students use computer-assisted program of IBM SPSS Statistics 21.The results showed that the use of the media learning in MI An-Nur Deyangan in the category quite nicely. This is evidenced by the views of the average value of 18.66 or 19 are included in this category is good enough. Speaking skills fall into the category is good enough, it is seen from the average value of an or 21 20.72 entered in that category pretty well. the analysis of the product moment gleaned value rxy count of 0.782. Those results showed Ho denied and Ha was accepted, that there is influence by learning media use speaking skills on the Indonesia language subjects in MI An-Nur Deyangan Magelang Regency.